INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI NYADRAN SEBAGAI UPAYA PENGUATAN KARAKTER ANAK BERBASIS KEARIFAN LOKAL DI DESA SETREN - Muhammad Mishbahul Muniir; Asyrul Hanni Adha; M. Rifqi Abdillah (LPPM IAD Probolinggo, 2026)
Nyadran is a form of local wisdom within Javanese society that embodies the interaction between religious and cultural values in community life. This study aims to analyze the values embedded in the Nyadran tradition in Setren Village, identify the challenges of integrating Islamic teachings with local cultural practices, and examine their implications for local wisdom-based Islamic Religious Education (IRE). This research employed a qualitative approach using an intrinsic case study design. Data were collected through participant observation, in-depth interviews, and documentation, and were analyzed using descriptive-analytical techniques involving data reduction, data display, and conclusion drawing. The findings reveal that the Nyadran tradition contains Islamic values, such as collective prayers, almsgiving, and the strengthening of social solidarity, alongside cultural values that preserve community identity and cohesion. However, several practices were also identified that potentially conflict with Islamic teachings, including requests made to sacred sites (punden) and entertainment activities associated with immoral behavior. These challenges are influenced by limited religious literacy, weak value-filtering mechanisms, and a stronger emphasis on preserving tradition than on aligning it with Islamic principles. Consequently, ambiguity in religious understanding emerges, while the role of Islamic Religious Education in integrating religious and cultural values remains suboptimal. Therefore, IRE should function as a filter, value reinforcer, and cultural reconstruction agent to ensure that local traditions are preserved while remaining consistent with Islamic values.